Pengaruh Perubahan Tarif Pajak Penghasilan, Struktur Modal Dan Kebijakan Dividen Terhadap Harga Saham - Rahayu, Puji; Yani, Ahmad (Universitas Gorontalo, 2021)
The purpose of this study is to analyze the effect of changes in income tax rates according to PP no. 30 of 2020, capital structure and dividend policy on stock prices in manufacturing companies in the Food and Beverage sector listed on the Indonesia Stock Exchange in 2016 –2020. This type of research uses descriptive quantitative. The population in this study were 30 companies. The sampling technique in this study was purposive sampling, so that a sample of 15 data from 3 companies was obtained for 5 years. Methods of data analysis using multiple linear regression analysis with the help of SPSS application. The results of the partial analysis show that the tax rate and dividend policy have no effect on stock prices. While the capital structure has a positive influence on stock prices. However, simultaneously stock prices are affected by changes in income tax rates, capital structure, and dividend policy. Based on the results of the study, it can be concluded that the high and low tax rates are not able to affect stock prices. the higher the capital structure will be followed by an increase in stock prices. While the dividend policy can not affect changes in stock prices.